An Integrated ANP and MARCOS for Green Supplier Selection: A Case Study on Construction Industry - Shanty Kusuma Dewi; Zara Safira Ramadhani (Department Industrial Engineering, University of Muhammadiyah Malang, 2022)
Raw material suppliers are important in production, especially in the construction industry. It is because suppliers determine the availability of raw materials in a project. The research aims to propose a new integrated procedure for Green Supplier Selection in the Construction Industry. The proposed integration method is Analytical Network Process (ANP) and Measurement Alternatives and Ranking according to Compromise Solution (MARCOS) method. Both methods are Multi-Criteria Decision Making (MCDM) procedures. The ANP method is used to determine the weight of each criterion, and the MARCOS method is used to determine the weight of the best supplier. Seventeen criteria are used in supplier selection involving economic and environmental dimensions. The results showed that based on the ANP method, the most important criterion was the consistent quality of goods. Meanwhile, three suppliers were analyzed for selection based on the MARCOS procedure. The results show that the best supplier is supplier X with a utility function value of 0.749. These results show that the proposed procedure (integration of ANP and MARCOS) effectively solves Green Supplier Selection.